2017
DOI: 10.1016/j.stemcr.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Dermal Fibroblasts into Osteo-Chondrogenic Cells with Elevated Osteogenic Potency by Defined Transcription Factors

Abstract: SummaryRecent studies using defined transcription factors to convert skin fibroblasts into chondrocytes have raised the question of whether osteo-chondroprogenitors expressing SOX9 and RUNX2 could also be generated during the course of the reprogramming process. Here, we demonstrated that doxycycline-inducible expression of reprogramming factors (KLF4 [K] and c-MYC [M]) for 6 days were sufficient to convert murine fibroblasts into SOX9+/RUNX2+ cellular aggregates and together with SOX9 (S) promoted the convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Recently reported that fibroblast cells successfully reprogrammed into neuronal cells by single and multiple factors, [ 27 , 28 ]. Several studies successfully converted the mammalian (human and animals) fibroblast cells into cardiomyocytes, hepatocytes and pancreatic cells and so on [ 29 30 ]. Besides, dermal fibroblasts are used as a neurodegenerative disease marker too [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported that fibroblast cells successfully reprogrammed into neuronal cells by single and multiple factors, [ 27 , 28 ]. Several studies successfully converted the mammalian (human and animals) fibroblast cells into cardiomyocytes, hepatocytes and pancreatic cells and so on [ 29 30 ]. Besides, dermal fibroblasts are used as a neurodegenerative disease marker too [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reprogrammed cells may also represent a breakthrough in the future obtaining of scalable cell sources capable of undergoing endochondral ossification. Specifically, dermal fibroblasts directly reprogrammed through into the chondrogenic lineage doxycycline-inducible human Sox9 were capable of promoting endochondral ossification in vivo [88, 89].…”
Section: Bone Development Mechanismsmentioning
confidence: 99%
“…Transdifferentiation is a process in which adult, mature and fully differentiated cells differentiate into another specific terminal cell type via the induction of lineage-specific transcription factors. Previous studies have revealed that fibroblasts can be converted into several lineages, including neurons (62), cardiomyocytes (63), hepatocytes (64) and osteoblasts (65,66) via the ectopic expression of multiple lineage-specific transcription factors or microRNAs (67). Importantly, this approach has also been applied in vivo using a number of lineage-specific transcription factors (68).…”
Section: Introductionmentioning
confidence: 99%